On a decomposition of the Witt group into direct sum of cyclic groups - Kozioł, Krzysztof (Annales Mathematicae Silesianae, 1992)
In the paper it is shown that the Witt group of the rational function field in countably many variables over a real-closed field can be decomposed into direct sum of cyclic groups. This is an example that the sufficient conditions given in [3] are not necessary.